Retraction Note: The Spiritual Dimension of Death: A Mini Review - Çaksen, Hüseyin (Journal of Pediatric Intensive Care, 2024)
The above article published in Journal of Pediatric Intensive Care on November 21, 2022 (DOI: 10.1055/s-0042-1758739), has been retracted as it is lacking scientific base.